ADMINISTRATORS NEED TO BE MINDFUL OF ROLES OF ACADEMICIANS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
LANGKAWI, KEDAH, 7 October 2015 – Administrators need to be aware, as well as to assume the roles of academicians to accommodate for the need to be knowledgeable in administrative operations, and in producing administrators who are versatile; similarly to the academicians who are required to have an understanding on various matters including administration, in addition to the knowledge in academics and research.